Hot Ductility and Fracture Phenomena of Low‐Carbon V–N–Cr Microalloyed Steels. Issue 1 (30th October 2019) - Liu, Yue; Du, Lin-Xiu; Wu, Hong-Yan; Misra, R. Devesh Kumar
Abstract : The hot ductility of low‐carbon V–N–Cr microalloyed steel is studied using a thermomechanical simulator. The steel is solution treated at 1350 °C and cooled at 15 °C s −1 to the test temperature in the range of 650–1200 °C. Next, they are strained to failure at a strain rate of 4 × 10 −3 or 4 × 10 −2  s −1, and ductility troughs are obtained. The results reveal a ductility trough in V–N–Cr steels in the range of 650–900 °C with a minimum reduction in area (RA) value of 13.5 % at 800 °C and strain rate of 4 × 10 −3  s −1 . The occurrence of dynamic recrystallization from 950 to 1200 °C has a substantial contribution to high ductility and on the formation of film‐like ferrite at prior austenite grain boundaries. The fracture mechanism changes from intergranular to highly ductile microvoid coalescence in the temperature range of 800–1200 °C and at a higher strain rate. Ductility loss in the V–N–Cr steel is caused by the presence of a high density of VN and/or V(C, N) precipitates, which are linearly present within the matrix, and a small number of random precipitates are present at the boundary. Abstract : The hot ductility of V–N–Cr microalloyed steel is strained to failure at a strain rate of 4 × 10 −3  s −1 or 4 × 10 −2  s −1, and ductility troughs are obtained in the range of 650–900 °C. Ductility loss in the V–N–Cr steel is caused by the presence of high density of VN precipitates.